2001
DOI: 10.1034/j.1600-0501.2001.012002179.x
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐abutment and peri‐abutment mucosal enlargement with mandibular implant overdentures

Abstract: A variety of terms have been used to describe changes in the oral mucosa around abutments underneath fixed and removable implant prostheses such as mucosal inflammation, peri-implant mucosal hyperplasia, gingival hyperplasia, hyperplastic tissue, mucosal proliferation, proliferative gingivitis and peri-implant mucositis. Although such terms have become part of the evidence-based literature, there is no histological evidence to support the descriptive terminology used by authors. The use of the alternative term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 52 publications
0
15
0
2
Order By: Relevance
“…The authors found the collection and analysis of data on clinical peri-implant parameters valuable and important for the monitoring, maintenance, and followup of the peri-implant tissues of patients rehabilitated with mandibular implant overdentures, particularly in view of the unique environment underneath the overdentures and also in view of the fact that late failures (following successful prosthodontic rehabilitation) have been reported in the l i t e r a t~r e .~>~~>~O Likewise, the rela-tion between peri-implant pathogenic microorganisms and inflammation of the marginal tissues has been confirmed and reported by several researcher^.^^^^^^^^ A recent review of the pertinent literature regarding mandibular implant overdentures has shown that biologic complications, such as mucosal enlargement, can be seen in between 4% and 44% of patients without strict oral hygiene control. 45 In the present study, healthy peri-implant mucosal conditions were maintained throughout the observation period with only small changes in the parameters measured. Plaque scores showed a tendency to reduce by the end of the first year, but this reduction had not been maintained by the end of the second year.…”
Section: Discussionmentioning
confidence: 82%
“…The authors found the collection and analysis of data on clinical peri-implant parameters valuable and important for the monitoring, maintenance, and followup of the peri-implant tissues of patients rehabilitated with mandibular implant overdentures, particularly in view of the unique environment underneath the overdentures and also in view of the fact that late failures (following successful prosthodontic rehabilitation) have been reported in the l i t e r a t~r e .~>~~>~O Likewise, the rela-tion between peri-implant pathogenic microorganisms and inflammation of the marginal tissues has been confirmed and reported by several researcher^.^^^^^^^^ A recent review of the pertinent literature regarding mandibular implant overdentures has shown that biologic complications, such as mucosal enlargement, can be seen in between 4% and 44% of patients without strict oral hygiene control. 45 In the present study, healthy peri-implant mucosal conditions were maintained throughout the observation period with only small changes in the parameters measured. Plaque scores showed a tendency to reduce by the end of the first year, but this reduction had not been maintained by the end of the second year.…”
Section: Discussionmentioning
confidence: 82%
“…1991; Zarb 1991). However, in a review of the relevant literature, 60% of studies on mandibular implant overdentures at that time were found to report mucosal enlargement underneath the prosthesis (Payne et al. 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This result is probably because of the fact that the bar is usually placed close to the mucosa because of space limitations. 20 Up-to-date evidence from the literature indicates that peri-implant soft tissue health is not affected by either ball or bar attachments. However, there is published evidence that shows a higher plaque index associated with magnet-type attachments.…”
Section: Soft Tissuementioning
confidence: 99%